Voltage-gated ion channels as novel regulators of epithelial ion transport in the osmoregulatory organs of insects - Dates, Jocelyne; Kolosov, Dennis (Frontiers in Insect Science, 2024)
Voltage-gated ion channels (VGICs) respond to changes in membrane potential (Vm) and typically exhibit fast kinetic properties. They play an important role in signal detection and propagation in excitable tissues. In contrast, the role of VGICs in non-excitable tissues like epithelia is less studied and less clear. Studies in epithelia of vertebrates and invertebrates demonstrate wide expression of VGICs in epithelia of animals. Recently, VGICs have emerged as regulators of ion transport in the Malpighian tubules (MTs) and other osmoregulatory organs of insects. This mini-review aims to concisely summarize which VGICs have been implicated in the regulation of ion transport in the osmoregulatory epithelia of insects to date, and highlight select groups for further study. We have also speculated on the roles VGICs may potentially play in regulating processes connected directly to ion transport in insects (e.g., acid-base balance, desiccation, thermal tolerance). This review is not meant to be exhaustive but should rather serve as a thought-provoking collection of select existing highlights on VGICs, and to emphasize how understudied this mechanism of ion transport regulation is in insect epithelia.